Inclusion Policies in the Tuition of Teacher Training of Students from the Early Childhood Education Training - Montiveros Garro, María Luján (2025)
This article reflects on a pedagogical intervention aimed at supporting university students and promoting educational inclusion in teacher training programs, particularly in the Early Childhood Education Program in Argentina. The intervention is part of a Consolidated Research Project titled Changes and Trends in Higher Education: Policies, Subjects, and Practices. Perspectives from Education and Philosophy. The project adopts a qualitative research framework, specifically utilizing the epistemological and methodological criteria of biographical-narrative research. Data collection techniques included surveys, participant observation, and interviews. Initial findings highlight the importance of designing training strategies focused on supporting first-year students to enhance and develop the cognitive skills required within the academic culture of higher education. Equally significant is the process of academic guidance and the “educational support provided by the teacher” (Onrubia, 2016, p. 4) to ensure student retention and continuity in their studies. The study underscores the urgent need to analyze policies and practices in the university context that address student admission, retention, and graduation, aligning these efforts with the institution's core objectives. Consequently, this research advocates for a critical review of the formative practices shaping universities to strengthen their mission and enhance their impact.